Environment - Raven, Peter H. (John Wiley and Sons, 2004)
The key to a sustainable future lies with students. It is their passion, their understanding of the issues, and most of all their choices that will shape the future of our planet. As it has through three previous editions, Peter Raven and Linda Berg's Environment gives students all the skills and tools they need to make the right choices for a sustainable environment! It teaches them how to think, rather than what to think, and prepares them for a lifetime of decision making about the environment. Students receive a scientific/thematic framework to use to make the right choices for a sustainable future